2014
DOI: 10.1007/s00404-014-3316-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of trans-vaginal mesh repair using the Prolift™ kit for pelvic organ prolapse at 4 years median follow-up in a tertiary referral centre

Abstract: Our study demonstrates that Prolift™ vaginal mesh surgery offers anatomical cure rates of 89.9 %. A higher rate of de novo recurrence in the non-operated compartment was noted suggesting that surgical correction in one compartment may exacerbate recurrence in other compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
5
9
0
Order By: Relevance
“…With respect to the anatomical results, we found a 91,3% of POP correction. This high percentage correlates to what is reported in the literature, ranging from 79 to 96,5% [10,[22][23][24]. The patients in whom there was a prolapse recurrence, they did not need a reoperation, as they remained asymptomatic, unlike other series [25].…”
Section: Commentsupporting
confidence: 86%
See 2 more Smart Citations
“…With respect to the anatomical results, we found a 91,3% of POP correction. This high percentage correlates to what is reported in the literature, ranging from 79 to 96,5% [10,[22][23][24]. The patients in whom there was a prolapse recurrence, they did not need a reoperation, as they remained asymptomatic, unlike other series [25].…”
Section: Commentsupporting
confidence: 86%
“…In those articles reporting urinary symptoms, the correction is the most common result [26,27]. Some authors found de novo SUI after the surgery (as well as we did); others reported a worsening of urinary symptoms [22,24], including voiding difficulty [28].…”
Section: Commentsupporting
confidence: 77%
See 1 more Smart Citation
“…High anatomic cure rates following mesh repair with a 5 % mesh exposure rate was noted in a single centre observational study [17]. Mesh exposure rates in our study population were noted to be 4 % (n = 6/135) and 2 % (n = 4/135) reported dyspareunia in our group.…”
Section: Discussionsupporting
confidence: 56%
“…The decrease mostly derived from fewer intraoperative bladder perforations and fewer surgical interventions to treat mesh complications during follow-up. For transvaginal Prolift® mesh, bladder perforation rates range between 0 and 2 % [8][9][10] and for ten different pooled kits this rate was reported to be 0.8 % [11]. A strength of our study was that bladder injury was confirmed or refuted by cystoscopy in nearly all patients and it may be assumed that the occurrence of 1.5 % bladder perforations is accurate.…”
Section: Discussionmentioning
confidence: 82%